Religiositas dan Perilaku Cybersex Pada Kalangan Mahasiswa - Ike Agustina; Fauzan Hafiza (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
This study aimed to determine the relationship between religiosity with cybersex behaviors in students. The hypothesis is There is a negative relationship between religiosity cyberesex behavior in undergraduate students. Someone religiosity is inversely proportional to his cybersex behavior. Subjects in this study are 52 people undergraduates student who lived in Yogyakarta . Data collection tool using scales that are Cybersex Behavior Scale and Religiosity Scale. The results of data analysis showed r = -0.333, with a significance level of 0008 (p <0.01). Based on the correlation results can be stated that there is a negative relationship between the religiosity of a cybersex behavior, so the hypothesis that there is a negative relationship between religiosity with cybersex behavior is acceptable. The coefficient of determination (R) obtained = 0.111 means that the contribution to the decline in religiosity variable rate of 11.1% CONDUCT cybersex.Keywords: Religiosity, Cybersex